Serum exosomal miR-122-5p, GAS, and PGR in the non-invasive diagnosis of CAG - Liu Naihua (De Gruyter, 2021)
The aim of this study was to integrate the serum exosomal miRNA miR-122-5p with canonical serological biomarkers for the non-invasive screening of chronic atrophic gastritis (CAG) patients.